Jerat 30 Persen Belanja Pegawai dan Mutu Layanan Daerah - Baren Sipayung; Agus Prasetyo (CV. Kurnia Grup, 2026)
This article analyzes the legal and institutional implications of the 30 percent cap on regional employee spending in Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. This policy was originally formulated to improve the quality of regional spending, expand the fiscal space for public services, and reduce the tendency for the Regional Budget (APBD) to be absorbed by bureaucratic costs. However, at the implementation level, the cap, read narrowly as a numerical target, can create tensions with the legal obligations of regional governments as employers, particularly in fulfilling the financial rights of state civil servants, including Government Employees with Employment Contracts. Using a normative juridical approach enriched by document studies and case illustrations of complaints from PPPK (Regional Employee Compensation Officers) in Tarakan City, this article demonstrates that late payment of Employee Income Supplements is not merely an administrative issue but can develop into a public service risk, accrual accounting risk, audit risk, and risk to the legitimacy of regional government. The study's findings emphasize the need for an adaptive implementation model: employee spending control remains in place, but must be accompanied by ASN needs planning, data validation, obligation recognition, and service performance measurement. This article recommends that the 30 percent limit not be used as an excuse to delay the rights of civil servants, but rather be positioned as an entry point for organizational reform, performance-based remuneration, and strengthening regional fiscal accountability.